Initiating luteal phase support with sc progesterone based on low serum progesterone on the transfer day in true natural cycle frozen embryo transfers - Demirel, Cem; Özcan, Pınar; Tülek, Fırat; Timur, Hikmet Tunç; Pasin, Özge (Frontiers in Endocrinology, 2023)
Abstract Introduction: Concerning contemporary in-vitro fertilization (IVF) practice, the use of frozen embryo transfer (FET) cycles has become more common than fresh transfers. Natural cycle (NC), programmed artificial cycle and mild stimulation cycle are primary endometrium preparation cycles. Monitoring serum progesterone levels in FET cycles are in the scope of current research focus. Low progesterone levels on the day of embryo transfer is presumed to negatively affect pregnancy outcomes, while progesterone supplementation may improve pregnancy rates. The purpose of our trial is to evaluate whether initiating subcutaneous (SC) progesterone supplementation on the day of embryo transfer when serum progesterone levels are below 10 ng/mL in tNC-FET will result in pregnancy rates comparable to those of patients with sufficient serum progesterone. Methods: Retrospective single centre study was conducted between August 2022 and April 2023 with 181 tNC-FETs. Patients were separated into groups according to serum progesterone concentrations (≥10 ng/mL and <10 ng/mL) on embryo transfer (ET) day. S.c progesterone (25 mg) was given on the day of ET when serum progesterone was <10 ng/mL, continuing until the 10th gestational week. Blood samples for pregnancy tests were collected 12 days after ET. Outcome parameters were pregnancy rate, clinical pregnancy rate (CPR), miscarriage rate, multiple pregnancy rate, biochemical pregnancy, and ongoing pregnancy rate (OPR). Results: About half (49.7%) had adequate progesterone concentrations (≥10ng/mL) on ET day. There was no significant difference between the groups regarding positive pregnancy test, OPR, multiple pregnancies, and miscarriage rates (57.8% versus 52.7%;34.4% versus 29.7%, 1.1% versus 2.2%;7.8% versus 5.5%; respectively, for progesterone concentrations on ET day ≥10ng/mL and <10ng/mL). With 55.2% of transfers leading to clinical pregnancy, significant differences emerged in biochemical pregnancy and CPR (3.3% vs 12.1%, P=0.02;54.4% vs 40.7%,P=0.03, for ≥10 ng/mL and <10ng/mL progesterone concentrations on ET day). Discussion: This study indicates that nearly half of the tNC-FETs may need luteal phase support due to low progesterone. However, 25 mc sc progesterone rescued the luteal support and yielded similar OPR as compared to normal progesterone group. Further studies are needed for understanding optimal progesterone levels, supplementation effectiveness, and potential benefits of earlier supplementation in FETs.